ISO 9001: Auditors give their verdict - Fonseca, Luís Miguel (2016)
The results of a survey we undertook of IRCA auditors show that respondents are of the opinion that the new edition of ISO 9001 is well aligned with both modern business management practices and quality principles. In addition, the results suggest that ISO 9001:2015 can provide significant added-value to the companies that choose to implement it. These summarised results, obtained as part of a wider academic research project aiming at assessing the impact of ISO 9001:2015, suggest that (according to the opinions of IRCA-certificated auditors) this new edition of the standard promotes and facilitates an improved alignment between quality and business best practices, thereby adding value to certified organisations.